Implementasi Kebijakan Surabaya Cross Culture International sebagai Upaya Pengembangan Pariwisata di Kota Surabaya - Hikmah, Dzakiyah Adalatul; Khusnul Prasetyo; Eka Arum Pramestya (Journal of Politics and Policy, 2022)
Every government, regardless of size, must constantly adapt to a changing environment and direct a change in a positive direction in which development is a key to do so.  The tourism industry is one of the few development fields that has consistently excelled.  The purpose of the Surabaya City Tourism and Culture Office, which bears the nickname "City of Heroes", is to increase tourist attraction through artistic and cultural performances.  In 2018, the Ministry of Tourism designated Surabaya as the winner of the “Best City” in Yokatta Wonderful Indonesia Tourism Awards.  The city government has made several initiatives to promote tourism.  The Surabaya City Government carried out preventive efforts in the form of the 2019 annual Surabaya Cross-Cultural International Themed Folk Art Festival. The focus of this research is to explain the implementation of Surabaya Cross Culture International activities and to describe the collaboration between government actors (government, civil society, and the private sector). This research is a descriptive qualitative research with interviews and literature review as the data collection techniques. The resource persons in the study were the Cultural Affairs Staff of the Surabaya City Culture and Tourism Office, the Head of Surabaya Local Parliament for the 2014–2019 period, and the Ning Representative for the City of Surabaya in 2019. The results of this study showed success eventhought there were several technical constraints in implementing the policy indicators proposed by Van Meter and Van Horn, namely the objectives and standards of the policy, the implementers’ attitude, resources, the implementers’ characteristics and communication between organizations and the economic, social, and political environment.  In addition, the collaboration carried out by the government, the private sector, and the community shows synergy to support the successful implementation of Surabaya Cross Culture International.